Development, safety and efficacy of sunscreen systems composed of rosmarinic acid, bemotrizinol and octyl p-methoxycinnamate - Candido, Thalita Marcilio (2023)
Progressively growing diagnoses of skin cancer trigger public and public health concerns about excessive sun exposure, awareness of the deleterious effects of ultraviolet (UV) radiation on the skin, and the proper use of sunscreens. Studies show that bioactive molecules, with special attention to phenolic compounds, such as rosmarinic acid (RA), may act to potentiate the photoprotective and antioxidant activity of cosmetic formulations. Through the review paper in Article 1, it is shown that, due to the range of methodologies available to verify skin conditions, it was possible to prove the effects of supplementation on the skin. A study involving supplementation with rosmarinic acid demonstrated its effects in protecting the skin against UVB rays, increasing skin elasticity and decreasing the depth of wrinkles; results attributed to the antioxidant properties of this molecule. Regarding the topical use of rosmarinic acid, the concepts of quality by design (QbD) were successfully used to design the formulations. From the results of the sun protection factor (SPF) and antioxidant activity, in vitro, prediction equations involving rosmarinic acid, bemotrizinol and octyl p-methoxycinnamate were obtained. It was verified that the presence of rosmarinic acid increased the antioxidant activity of the formulations, while decreasing the SPF. An increase in the photostability of the formulation containing the two sunscreens was also observed for the rosmarinic acid. Four samples were chosen for the assessment of comet assay and skin biocompatibility. Also, the evaluation of anti-inflammatory activity in vivo using laser doppler flowmetry was performed. Through comet assay, all samples protected DNA fragmentation, however, we did not attribute this finding to the presence of rosmarinic acid exclusively. By the in vivo tests, none of the formulations caused an alteration of the pH value of the skin surface or an increase in redness. All formulations provided increase in skin hydration after 30 minutes of application. However, only the formulations without rosmarinic acid provided increase in skin hydration after 7 days of application. An increase in transepidermal water loss (TEWL) was observed for F1, F2 and F4. We may conclude that both results (skin hydration and TEWL) were related to the composition of the vehicle containing or not the RA. In respect of the in vivo evaluation of anti-inflammatory efficacy, no decreases were observed in the inflammatory reaction caused by ethyl nicotinate, however, the sample containing rosmarinic acid presented an increase in the tangent value. In view of the specialized literature and our results, we may suggest that new in vivo tests should be carried out, with modifications in the protocol of application of the samples on the skin and even the investigation of other vehicles for the active ingredients.